The role of cultural artefacts as a tools to mediate common cultural practices in a multi- ethnic society - Perumal, Velu; Abd Rahman, Khairul Aidil Azlin; Raja Ahmad Effendi, Raja Ahmad Azmeer; Dolah, Mohd Shahrizal; Sinnappan, Santhidran (Universiti Putra Malaysia Press, 2019)
The concept of sustainability is not only associated with the environment, but includes cultural aspects. Whereby cultural artefacts help in the sustainability of any culture or cultural practice. Thus, cultural artefacts are believed to be the identity of a culture. On the other hand, cultural artefacts have become a mediator in developing common practices in diverse cultures. However, in a multi-ethnic and multi-cultural country like Malaysia, the plural and the autonomous cultural systems are seen as an obstacle in various common forms. As such this study aims to identify the commonly used cultural artefacts and the reasons for their preferences. The nominal group technique (NGT) was used in this study to identify the commonly used cultural artefacts. NGT is a qualitative data collection technique based on discussions among various categories of stakeholders and multi-ethnic group members. The study has justified the existence of common elements in multi-cultural practices which could reduce ethnocentrism and promote social integrity and unity among Malaysia’s multiethnic society.